2009
DOI: 10.1111/j.1582-4934.2009.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of muscle regeneration by local injection of muscle‐specific microRNAs in rat skeletal muscle injury model

Abstract: MicroRNA (miRNA)s are a class of non-coding RNAs that regulate gene expression post-transcriptionally. Muscle-specific miRNA, miRNA (miR)-1, miR-133 and miR-206 play a crucial role in the regulation of muscle development and homeostasis. Muscle injuries are a common muscloskeletal disorder, and the most effective treatment has not been established yet. The purpose of this study was to demonstrate that a local injection of double-stranded (ds) miR-1, miR-133 and 206 can accelerate muscle regeneration in a rat s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
163
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 196 publications
(168 citation statements)
references
References 38 publications
2
163
1
2
Order By: Relevance
“…miRNAs are short (ϳ20 -25 nucleotides) and noncoding RNA molecules, which repress gene expression by binding to the 3=-untranslated region of target mRNAs and either inhibit translation or promote cleavage of the transcript (1, 13). Recently, muscle-specific miRNAs miR-1, miR-133a, and miR206 have been shown to participate in the regulation of muscle mass (3,17,18,25,29). Some studies have reported that these miRNAs promote proliferation and differentiation of muscle cells (3,18,29), whereas miR-1 and miR-133a seem to be downregulated during skeletal muscle hypertrophy (17,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs are short (ϳ20 -25 nucleotides) and noncoding RNA molecules, which repress gene expression by binding to the 3=-untranslated region of target mRNAs and either inhibit translation or promote cleavage of the transcript (1, 13). Recently, muscle-specific miRNAs miR-1, miR-133a, and miR206 have been shown to participate in the regulation of muscle mass (3,17,18,25,29). Some studies have reported that these miRNAs promote proliferation and differentiation of muscle cells (3,18,29), whereas miR-1 and miR-133a seem to be downregulated during skeletal muscle hypertrophy (17,25).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, muscle-specific miRNAs miR-1, miR-133a, and miR206 have been shown to participate in the regulation of muscle mass (3,17,18,25,29). Some studies have reported that these miRNAs promote proliferation and differentiation of muscle cells (3,18,29), whereas miR-1 and miR-133a seem to be downregulated during skeletal muscle hypertrophy (17,25). Furthermore, upregulations of miR-1 in dexamethasone-mediated muscle atrophy in mice and atrophic signals, which are integrated by miR-1, have been reported (19).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several therapeutic trials regulating endogenous miRNA in vivo have been conducted [14][15][16]. miRNA also plays a crucial role in the pathogenesis of disease or trauma in locomotor organs [17][18][19][20][21]. As we known, vascular supply in tendons is very limited and is significantly reduced after injury or rupture.…”
Section: Introductionmentioning
confidence: 99%
“…Individual microRNAs (miRs) are known to target many mRNAs that control numerous cellular processes (17,18). A cluster of myomiRs including miR1, miR133, and miR206 plays a role in myogenesis and muscle regeneration (19,20). Both miR1 and miR133 were found to be down-regulated in skeletal muscle undergoing hypertrophy and it was proposed that Igf-1 mRNA may be negatively regulated by miR1 in skeletal muscle (21) and cardiac muscle (22).…”
mentioning
confidence: 99%